2006
DOI: 10.1108/09578230610674949
|View full text |Cite
|
Sign up to set email alerts
|

Sitting in the “hot seat”: new headteachers in the UK

Abstract: Purpose -This article aims to identify the main challenges faced by headteachers after taking up their first headship in the UK. It also compares how these challenges have changed over time. Other purposes include the setting of the initial phase of headship within a whole career model and how heads become socialised into the role. Design/methodology/approach -Based on evidence from empirical studies using longitudinal data over a period of 20 years, the paper reviews the challenges faced by new headteachers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 7 publications
1
64
0
1
Order By: Relevance
“…External changes such as greater competition between schools and accountability for academic results have widened the expectations of the role of the principal (Weindling & Dimmock, 2006). Moreover, the increased autonomy for schools in many countries through school-based management has greatly increased the role and importance of the principal as an autonomous leader.…”
Section: Professional Development For School Leaders In Generalmentioning
confidence: 98%
See 1 more Smart Citation
“…External changes such as greater competition between schools and accountability for academic results have widened the expectations of the role of the principal (Weindling & Dimmock, 2006). Moreover, the increased autonomy for schools in many countries through school-based management has greatly increased the role and importance of the principal as an autonomous leader.…”
Section: Professional Development For School Leaders In Generalmentioning
confidence: 98%
“…Moreover, they identified challenges that they encountered, including budget and finance, personnel management, information gathering, politics and self-learning. Weindling and Dimmock (2006), in a review of studies and using longitudinal data over a period of 20 years, concluded that the main difficulties faced by new heads include addressing the legacies of their predecessors, overcoming existing school culture and communication behaviours, dealing with the poor staff performance and a poor public image of the school.…”
Section: Contentmentioning
confidence: 98%
“…Research has found that schoolteachers often endow the previous principal with saintly virtues once they leave the school even though they noted their frailties while in post. Weindling and Dimmock (2006) introduce evidence about new principals working in the shadows of their predecessors. Their discussion supports Draper and McMichael's (2000) finding that seven out of ten new principals reported on issues brought about by the previous principal's style of management.…”
Section: The Life Of Beginning Principalsmentioning
confidence: 99%
“…Crow (2006) and Weindling and Dimmock (2006) note the dynamic and multifaceted nature of principal socialisation. Drawing upon data from a longitudinal study of British principals, the latter authors identify seven stages of socialisation.…”
Section: The Life Of Beginning Principalsmentioning
confidence: 99%
“…In the United States, for example, a teacher becomes eligible for promotion to the position of principal when they have completed a Masters in educational administration (Tucker & Codding, 2002), while in the United Kingdom, teachers must climb the ranks to become senior faculty, or "deputy headˮ, and must assist the principal during a minimum of five years before being allowed to apply for the position of headmaster (Weindling & Dimmock, 2006).…”
Section: The Context Of Reformmentioning
confidence: 99%